Acompañamiento en el proceso de intervención del TDAH desde la perspectiva del terapeuta, docente y padres - Martínez Teuta, Isabella (Universidad de San Buenaventura - Cali, 2019)
The objective of this research is the possibility of approaching the accompanying parents,therapist, and a teacher in a process of intervention in a case of attention Deficit Hyperactivity Disorder (ADHD). For this purpose it is important to inquire about the conception that they build each of the actors on the diagnosis, intervention strategies, and the factors that enable or hinder the approach jointly. The development of the research involved; a primary teacher, a psychologist, and the mother of a child diagnosed with ADHD. As a data collection strategy was made use of semi-structured in-depth interviews. Within the results highlights the articulation between the strategies of boarding and accompaniment in the process of the child,process that benefited looks for the interest, knowledge and communication of the three actors involved, allowing the child to improve emotional, academic, family and social aspects.